Stimulus Threat and Exposure Context Modulate the Effect of Mere Exposure on Approach Behaviors - Young, Steven G.; Jones, Isaiah F.; Claypool, Heather M. (Frontiers in Psychology, 2016)
Mere-exposure research has found that initially neutral objects made familiar are preferred relative to novel objects. Recent work extends these preference judgments into the behavioral domain by illustrating that mere exposure prompts approach-oriented behavior toward familiar stimuli. However, no investigations have examined the effect of mere exposure on approach-oriented behavior toward threatening stimuli. The current work examines this issue and also explores how exposure context interacts with stimulus threat to influence behavioral tendencies. In two experiments participants were presented with both mere-exposed and novel stimuli and approach speed was assessed. In the first experiment, when stimulus threat was presented in a homogeneous format (i.e., participants viewed exclusively neutral or threatening stimuli), mere-exposure potentiated approach behaviors for both neutral and threatening stimuli. However, in the second experiment, in which stimulus threat was presented in a heterogeneous fashion (i.e., participants viewed both neutral and threatening stimuli), mere exposure facilitated approach only for initially neutral stimuli. These results suggest that mere-exposure effects on approach behaviors are highly context sensitive and depend on both stimulus valence and exposure context. Further implications of these findings for the mere-exposure literature are discussed.